Ecoturism Potential and his Sustainable Development Oportunities in the Border Region between Slovakia and Poland - Čuka, Peter; Osuch, Wiktor (European Journal of Sustainable Development, 2018)
The aim of the paper is to identify the current state of ecotourism in Slovak - Polish borderlands. The research aims to identify the eco-tourism infrastructure, the motivation for using these facilities (by nationality) and economic behavior of tourists both on the Slovak and on the Polish side. The studied geographic zone is the area of the Western Carpathians in the Kysucká vyso?ina (Slovakia) and Beskyd ?ywiecki districts in Poland. Ecotourism has tradition in Slovakia since the 1960s. Unlike the Polish countryside, in Slovakia many agricultural activities have disappeared or transformed in the given period. This allowed the development of cottage tourism and rural tourism, which in Slovak conditions is, besides agrotourism, the most prominent representative of ecotourism. Slovakia, alongside Scandinavia, France, Italy and the Czech Republic, is among the leading European countries with a high share of second homes. After 1990, agro-tourism has been dynamized in Slovakia and Poland. For the studied area we consider the centers of ?adca in Slovak and ?ywiec on the Polish side - including their recreational background. In research were used methods of statistical analyzes of public data, field recognitioning, mystery shopping, but also qualitative methods for determining the tourist and economic behavior of ecotourism clients of the area under research. The study should highlight the real motives of eco-tourists' participation, the economic potential of ecotourism in the area and the main shortcomings that limit the future development of ecotourism. Keywords: Ecoturism, Slovak – Polish border region, motives for eco turism, tourists eco behavior